2017
DOI: 10.1002/ejsp.2343
|View full text |Cite
|
Sign up to set email alerts
|

Gaming motivation and problematic video gaming: The role of needs frustration

Abstract: Motivation is often used as a predictor of a problematic style of video game engagement, implying that individuals' gaming undermines optimal functioning. Drawing from recent advances in Self‐Determination Theory (SDT), the present study explores the links between gaming motivations, the daily frustration of basic psychological needs, and reports of problematic video gaming (PVG). A sample of 1029 participants (72.8% male; M = 22.96 years; SD = 4.13 years) completed items regarding their gaming engagement and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 48 publications
3
45
1
2
Order By: Relevance
“…A CFA supported an 11-item three-factor correlated model, consistent with prior research that has endorsed the robustness of the 11-item three-factor correlated structure (Hein et al, 2015;Martinent et al, 2015;Mills et al, 2018). Pearson's correlations obtained from the CFA showed high correlations between the three factors; though the upper limit of the 95% confidence interval did not exceed unity in any cases, supporting the adequate level of conceptual discrimination between the frustration of the BPNs for autonomy, competence, and relatedness proposed theoretically by SDT (Ryan & Deci, 2017.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A CFA supported an 11-item three-factor correlated model, consistent with prior research that has endorsed the robustness of the 11-item three-factor correlated structure (Hein et al, 2015;Martinent et al, 2015;Mills et al, 2018). Pearson's correlations obtained from the CFA showed high correlations between the three factors; though the upper limit of the 95% confidence interval did not exceed unity in any cases, supporting the adequate level of conceptual discrimination between the frustration of the BPNs for autonomy, competence, and relatedness proposed theoretically by SDT (Ryan & Deci, 2017.…”
Section: Discussionsupporting
confidence: 80%
“…Also, Pulido et al (2017) found problems related to internal consistency for the relatedness need frustration subscale. Previous research has also shown psychometric support for an 11-item, three-factor correlated model among Estonian students (Hein, Koka, & Hagger, 2015), French athletes (Martinent, Guillet-Descas, & Moiret, 2015), and U.S. video-game players (Mills, Milyavskaya, Heath, & Derevensky, 2018). Yet, Martinent et al (2015) detected internal consistency problems in the autonomy need frustration subscale.…”
Section: Introductionmentioning
confidence: 86%
“…It might be possible that engaging in an activity in an obsessive manner could temporarily restore the needs of the individual, which, however, rarely leads to adaptive outcomes of the activity. A recent study conducted by Mills, Milyavskaya, Heath, and Derevensky (2018) also supported the relevance of need frustration in relation to online gaming. Thus, the experience of general need frustration could be seen as a potential risk factor of OP.…”
Section: Need Satisfaction and Need Frustration As Predictors Of Passionmentioning
confidence: 72%
“…In a Taiwanese adolescent sample, Wan and Chiou found that the compulsive use of online games may be driven by the relief of need dissatisfaction, rather than the pursuit of satisfaction [22]. Other research only covered daily need frustration in their studies, and demonstrated how it could explain the increasingly problematic style of video gaming engagement in North American samples [23,24]. Collectively, previous research has suggested that psychological needs, especially when being dissatisfied, may predict IGD.…”
Section: Introductionmentioning
confidence: 99%